Design of a multimodal fibers optic system for small animal optical imaging. Issue 1 (February 2015) - Spinelli, Antonello E.; Pagliazzi, Marco; Boschi, Federico
Abstract Small animals optical imaging systems are widely used in pre-clinical research to image in vivo the bio-distribution of light emitting probes using fluorescence or bioluminescence modalities. In this work we presented a set of simulated results of a novel small animal optical imaging module based on a fibers optics matrix, coupled with a position sensitive detector, devoted to acquire bioluminescence and Cerenkov images. Simulations were performed using GEANT 4 code with the GAMOS architecture using the tissue optics plugin. Results showed that it is possible to image a 30 × 30 mm region of interest using a fiber optics array containing 100 optical fibers without compromising the quality of the reconstruction. The number of fibers necessary to cover an adequate portion of a small animal is thus quite modest. This design allows integrating the module with magnetic resonance (MR) in order to acquire optical and MR images at the same time. A detailed model of the mouse anatomy, obtained by segmentation of 3D MRI images, will improve the quality of optical 3D reconstruction.